PENGARUH FINANCIAL TECHNOLOGY DAN INKLUSI KEUANGAN TERHADAP KINERJA KEUANGAN YANG DIMEDIASI OLEH LITERASI KEUANGAN PADA USAHA MIKRO KECIL MENENGAH (UMKM) DI KOTA SEMARANG - Aisya, Rezky; Meiriyanti, Rita; Widiastuti, C. Tri (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2025)
This study aims to explore the connection between financial literacy, financial inclusion, and financial technology and financial performance. It also looks at whether financial literacy mediates the link between financial technology, financial inclusion, and financial performance, as well as if financial literacy impacts financial technology and financial inclusion. The research population consists of MSMEs in Semarang City, and 95 MSMEs in the Food and Beverage (FnB) sector in West Semarang were selected as a sample because of the researcher's proximity. A quantitative descriptive research approach was used in this investigation. The findings demonstrate that financial technology and financial inclusion have a major and positive influence on the financial performance of MSMEs in Semarang City. However, financial literacy is not much impacted by financial technology or financial inclusion. Instead, financial literacy impacts financial performance, and financial technology and financial inclusion have a positive and significant impact on financial performance through financial literacy.